COST ANALYSIS ON HYDROGEN REFUELING STATION USING OPERATIONAL, STORAGE, AND DISTRIBUTION MODEL SIMULATION - Roesiana Dewi, Aisshah; Sumantri, Yeni; Kusumaningdyah, Widha; Hanafi Ichsan, Mochammad Hannats; Irawan, Yudy Surya (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2025)
The burgeoning interest in low-emission mobility has led to a focus on Hydrogen Refueling Stations (HRS) in developing nations such as Indonesia. This study, unique in its assessment of the techno-economic feasibility of two distinct HRS configurations, delves into the cascade storage system, which involves storing hydrogen in a series of pressure vessels, and the booster compressor system, which utilizes a compressor to elevate the hydrogen's pressure. The evaluation considers projected daily demand scenarios of 413 kg/day and local economic factors adjusted for inflation. A meticulous and comprehensive discrete event simulation model was developed to encapsulate the operational dynamics inherent in each scenario under consideration. This model, which incorporates key factors such as fueling time, cascade priority logic, and hourly vehicle arrival patterns, ensures that the audience is fully informed and knowledgeable about the study's findings. In conjunction with this, an economic analysis was conducted employing the robust Levelized Cost of Hydrogen (LCOH) and Rate of Return (ROR) frameworks. The study utilized specified financial parameters, including a 5.75% real discount rate, a 15-year analytical horizon, and cost adjustments to reflect the 2025 Indonesian Rupiah. The model aims to provide a robust understanding of hydrogen fueling systems' economic viability and operational efficiency in the specified context through these methodologies. The results show that the cascade system yields a lower LCOH (IDR 41.017/kg) and capital cost per kg compared to the booster system (IDR 70.833/kg). However, both reach breakeven within 9.5 years. The booster is less advantageous in smaller-scale deployments because of its higher compression efficiency and capital investment requirements. The higher requirement for capital investment and compressing efficiency. The economic feasibility of HRS configurations may be considerably enhanced by methods to boost hydrogen sales and control capital expenditure, providing a bright future for hydrogen fueling systems.